Production systems and breeding practices of Begaria cattle breed as input for a community-based breeding program - Tesfalem Aseged; Tesfaye Getachew; Sandip Banerjee; Teklewold Belayhun; Awoke Melak; Aweke Engdawork; Esho Kefyalew; Abraham Assefa; Abebe Hailu (Heliyon, 2023)
This study aimed to describe the production systems and breeding practices of Begaria cattle breeds as a resource for community-based conservation and breeding program. A semi-structured questionnaire and focus group discussions were employed to identify and describe the breeding practice of the farmer. Three kebeles: Almahal, Fanguso, and Mankush were considered for the study. The data were analyzed using R software. Cattle were kept for a variety of reasons, including milk, breeding, meat, cash, and saving. It was typical throughout the study area to see herd mixing and keeping together (4.7 ± 0.33 herds on average), herd movement during the dry season, and breeding bull sharing (1.9 ± 1.55 shared bulls). During the summer season, cattle rearing in the areas was hindered by feed and water shortages. The breed's major reproduction constraints were abortion (24 %), repeat breeding (19), and calf mortality (14). The primary reason for keeping Begaria cattle was for milk (29 %), cash (26), meat (22), and breeding (0.22). The average age at first calving (AFC), calving interval (CI) and milk yield per day of the breed were 41.5 ± 1.63, 16.0 ± 0.43 months, and 3.2 ± 0.12 L respectively. The average age of breeding bull selection was 3 ± 0.1 years, and it was based on several criteria, including their phenotype, growth, and white coat colour. Based on the current findings, it is recommended that a multi-trait selection program be designed with full stakeholder participation.